A Two-Stage Algorithm of Numerical Evaluation of Integrals in Number-Theoretic Methods (Journal of Computational Mathematics, 1999)
To improve the numerical evaluation of integrals in Number-Theoretic Methods, we give a two-stage algorithm. The main idea is that we distribute the points according to the variations of the quadrature on the subdomains to reduce errors. The simulations results are also given.
Keywords: Numerical integration; Monte Carlo method; Number-theoretic method.